Grapes (Vitis vinifera) as a Potential Candidate for the Therapy of the Metabolic Syndrome. (22nd January 2016) - Akaberi, Maryam; Hosseinzadeh, Hosein
Abstract : Metabolic syndrome is associated with several disorders, including hypertension, diabetes, hyperlipidemia as well as cardiovascular diseases and stroke. Plant‐derived polyphenols, compounds found in numerous plant species, play an important role as potential treatments for components of metabolic syndrome. Studies have provided evidence for protective effects of various polyphenol‐rich foods against metabolic syndrome. Fruits, vegetables, cereals, nuts, and berries are rich in polyphenolic compounds. Grapes ( Vitis vinifera ), especially grape seeds, stand out as rich sources of polyphenol potent antioxidants and have been reported helpful for inhibiting the risk factors involved in the metabolic syndrome such as hyperlipidemia, hyperglycemia, and hypertension. There are also many studies about gastroprotective, hepatoprotective, and anti‐obesity effects of grape polyphenolic compounds especially proanthocyanidins in the literature. The present study investigates the protective effects of grape seeds in metabolic syndrome. The results of this study show that grape polyphenols have significant effects on the level of blood glucose, lipid profile, blood pressure, as well as beneficial activities in liver and heart with various mechanisms. In addition, the pharmacokinetics of grape polyphenols is discussed. More detailed mechanistic investigations and phytochemical studies for finding the exact bioactive component(s) and molecular signaling pathways are suggested. Copyright © 2016 John Wiley & Sons, Ltd.